2004
DOI: 10.1074/jbc.m313762200
|View full text |Cite
|
Sign up to set email alerts
|

The Residue 129 Polymorphism in Human Prion Protein Does Not Confer Susceptibility to Creutzfeldt-Jakob Disease by Altering the Structure or Global Stability of PrPC

Abstract: There are two common forms of prion protein (PrP) in humans, with either methionine or valine at position 129. This polymorphism is a powerful determinant of the genetic susceptibility of humans toward both sporadic and acquired forms of prion disease and restricts propagation of particular prion strains. Despite its key role, we have no information on the effect of this mutation on the structure, stability, folding, and dynamics of the cellular form of PrP (PrP C ). Here, we show that the mutation has no meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
76
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 61 publications
9
76
0
Order By: Relevance
“…This region of the protein is predominantly unstructured, as indicated by 15 N relaxation rates (6,14). However, previous studies have indicated that this region of the protein may be exchanging between more structured or collapsed states, as it exhibits differential peak intensities (14), and residues 105-126 appear to be capable of forming intra-and/or intermolecular interactions in full-length ␤-PrP oligomers (35).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…This region of the protein is predominantly unstructured, as indicated by 15 N relaxation rates (6,14). However, previous studies have indicated that this region of the protein may be exchanging between more structured or collapsed states, as it exhibits differential peak intensities (14), and residues 105-126 appear to be capable of forming intra-and/or intermolecular interactions in full-length ␤-PrP oligomers (35).…”
Section: Resultsmentioning
confidence: 93%
“…Equilibrium Denaturation Data Monitored by CD-The amide CD absorption of 50 M ␤-PrP in 10 mM sodium acetate, 2 mM sodium azide, 2 mM DTT, pH 4.0, was recorded in varying concentrations of urea as previously described (6,13). The mean residue ellipticity signal ([ ]r) at 215 nm was converted to the proportion of molecules in the unfolded state, ␣ U , according to the relationship,…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identity of the amino acid at position 129 has a significant impact on infectious, sporadic, and familial prion diseases. Although the importance of the polymorphism has been well documented, studies have only revealed slight effects of the substitution on prion stability and conversion (28,29) and a possible effect on the kinetics of amyloid formation (30).…”
Section: Resultsmentioning
confidence: 99%